2016
DOI: 10.18632/oncotarget.12707
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of fibulin-3 for malignant pleural mesothelioma: A systematic review and meta-analysis

Abstract: BackgroundSeveral studies have investigated the diagnostic value of fibulin-3 for malignant pleural mesothelioma (MPM), but the results were various. Therefore, we performed a systematic review and meta-analysis to evaluate the diagnostic value of fibulin-3 for MPM.ResultsEight studies were included in this work. The overall sensitivity of blood fibulin-3 were 0.87 (95% CI, 0.58 – 0.97) and 0.89 (95% CI, 0.77 – 0.95), respectively. The overall sensitivity and specificity of PF fibulin-3 for MPM were 0.73 (95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…We reported non-signi cant difference in the diagnostic validities of survivin and bulin-3 in diagnosing lung cancer or predicting MPM. Although no published data regarding the utility of survivin in diagnosing lung cancer, humoral bulin-3 test data published revealed high variability among studies and still remains a contentious issue (38). A meta-analysis study reported that blood bulin-3 is useful for MPM diagnosis and its validity was higher than soluble mesothelinrelated peptides (SMRP) and osteopontin (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported non-signi cant difference in the diagnostic validities of survivin and bulin-3 in diagnosing lung cancer or predicting MPM. Although no published data regarding the utility of survivin in diagnosing lung cancer, humoral bulin-3 test data published revealed high variability among studies and still remains a contentious issue (38). A meta-analysis study reported that blood bulin-3 is useful for MPM diagnosis and its validity was higher than soluble mesothelinrelated peptides (SMRP) and osteopontin (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although no published data regarding the utility of survivin in diagnosing lung cancer, humoral bulin-3 test data published revealed high variability among studies and still remains a contentious issue (38). A meta-analysis study reported that blood bulin-3 is useful for MPM diagnosis and its validity was higher than soluble mesothelinrelated peptides (SMRP) and osteopontin (38). Few studies could be traced in literature and reported similar ndings (37,39).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the overall sensitivity and specificity for blood fibulin-3 were 0.87 [95% confidence interval (CI) 0.58-0.97] and 0.89 (95% CI 0.77-0.95), respectively. Based on these results, they concluded that fibulin-3 is a useful diagnostic biomarker for MM [47]. Similarly, Pei et al reported that fibulin-3 confers a relatively high diagnostic efficacy and could be acceptable as an auxiliary biomarker to aid in MM identification [32].…”
Section: Fibulinmentioning
confidence: 93%
“…Several studies have investigated the diagnostic value of fibulin-3 for MPM and based on these fibulin-3 results a useful diagnostic marker for MPM (30)(31)(32)(33)(34).…”
Section: Fibulin-3mentioning
confidence: 99%